Analisis Efektivitas Program Skill Development Center (SDC) Terhadap Penurunan Angka Pengangguran Terdidik di Kota Surakarta: Analisis Efektivitas Program Skill Development Center (SDC) Terhadap Penurunan Angka Pengangguran Terdidik di Kota Surakarta - Hastuti, Triatmi Puji; Sabandi, Muhammad; Wahyono, Budi (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Skill Development Center is one of the priority programs aimed at overcoming employment problems. Academic (training institutions), business (industrial world), government (government), and community (professional association) are the four key entities that are stakeholders in enhancing HR capability. Analyzing how well the SDC program works to lower educated unemployment in Surakarta City is the aim of this study. This study employed a qualitative literature study approach as its research methodology. Investigating the state of natural objects is known as qualitative research. The Surakarta City Central Statistics Agency's data documentation, the Surakarta City Manpower Office's data, and scholarly publications were the data collecting methods employed in this study. The Surakarta City Central Statistics Agency's (BPS) official statistics data serves as the primary source of information. The policy implementation theory of Van Meter and Van Horn (1975) is applied in this study. This theory describes the elements that affect how well public policies work, including the policy's goals and scale, available resources, interorganizational communication, the traits of implementing agents, social, political, and economic circumstances, and the attitudes of implementers. The SDC program is able to reduce the number of educated unemployed in Surakarta City, because the unemployment rate has decreased in the past three years.